Anti-inflammatory and immunomodulatory effect of purslane and turmeric in rheumatoid arthritis rat models: Purslane and turmeric effects on RA in rats - Rasool, Dween Faqi; Hiwa Ramadhan Fatah; Emad Khelil Mohammed Zangana (Cellular and Molecular Biology, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by joint inflammation. Given the side effects of conventional treatments, this study focuses on the anti-inflammatory effects of purslane (Portulaca oleracea) and turmeric (Curcuma longa). The research is driven by the growing demand for plant based-treatment for safer therapeutic options for RA management. Five groups were formed; the control group included only healthy rats and was used for baseline comparison. RA was experimentally induced in male rats using Complete Freund’s Adjuvant (CFA). Treated groups received extracts of purslane, turmeric and combination of both and one group was left untreated (RA group). Bioactive compounds in plant extracts were identified by GC-MS analysis. Paw edema and body weight were monitored thrice weekly for statistical analysis, and neutrophil counts were assessed microscopically. Enzyme-linked immunosorbent assay (ELISA) was used to quantify the inflammatory biomarkers including IL-1, TNF-α, IL-6, IL10, CD14, CD4, MMP-1, alongside measuring cyclic citrullinated peptide (anti-CCP) levels. CFA-induced RA significantly increased paw edema, neutrophil counts (P<0.0001), and elevated levels of anti-CCP, CD4, IL-1, IL-6, and TNF-α compared to the control group (P<0.001). Treatments with purslane, turmeric and combination reduced paw swelling and these inflammatory markers in RA induced rats significantly (P< 0.01). Despite the increasing serum level of MMP-1, CD14 and IL-10 the reduction by plant extract did not show significant results. It is concluded that the bioactive compounds in the purslane and turmeric have anti-inflammatory effects through reducing inflammatory markers in RA induced rats.